Bacterial diversity changes in response to an altitudinal gradient in arid and semi-arid regions and their effects on crops growth - Zakavi, Maryam; Askari, Hossein; Shahrooei, Mohammad (Frontiers in Microbiology, 2022)
The microbiome of soil has a fundamental role in the maintenance of soil and plants. While the diversity of microbes is one of the most important factors of environments, little is known about elevation effects on the microbiome and the impact of the affected microbiome on plants. The main goal of this study is to expand our knowledge of what happens to the soil bacterial community along an altitudinal gradient and investigate their possibly different impacts on plant growth. To find the effects of elevational gradient on the microbiome and plant growth, bacteria of soils at various altitudes have been isolated characterized and identified by Matrix-Assisted Laser Desorption/Ionization-Time of Flight Mass Spectrometry (MALDI-TOF MS). Furthermore, their effect has been investigated by isolates assessment on maize, wheat, and canola. Based on our results higher altitude results in a higher diversity of the microbiome and lower bacteria biomass. Bacillus cereus is found in abundance in arid and semi-arid samples. It is interesting that enhanced diversity in higher altitude show similarity in response to environmental stress and tolerate these factors well. Furthermore, the inoculation of these bacteria could enhance the overall growth of plants. We provide evidence that bacterial communities could change their biomass and diversity in response to altitude changes. These indicate evolutionary pressure as these bacteria could tolerate stress factors well and have a better coexistence relationship with plants.